Working with people with learning disabilities : theory and practice - Thomas, David, 1962 April 24-; Woods, Honor, 1950- (London ; New York : Jessica Kingsley Publishers, 2003)
The authors of this guide bring together the relevant theory for social workers, nurses, teachers and others working with people with learning disabilities. Using jargon-free explanations and case examples they provide the theoretical understanding needed to inform good practice and help to improve the quality of life of the person with a learning disability. They discuss both psychological and practical theories, including: cognitive and behavioural approaches; systems approach; task centred approach; role theory. Emphasising empowerment and inclusion of those with learning disabilities, they.
Working with People with Learning Disabilities; Contents; Acknowledgements; Disclaimer; Introduction; 1 What is a Learning Disability?; 2 Application of Theory; 3 Anti-Discriminatory Practice and Anti-Oppressive Practice; 4 What is Normalization?; 5 Communication Methods; 6 Advocacy, Empowerment, Participation and Choice; 7 Universal Human Experience in the Lives of People with Learning Disabilities; 8 Values, Ethics and Contrasting Approaches: Person Centred and Behavioural; 9 Practical Theories and Methods; 10 Society's Influences on Practice; 11 The Way Forward; Conclusion; References.
Includes bibliographical references (pages 261-272) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Learning disabilities; Learning disabled children; Intellectual disability; Persons with Intellectual Disabilities -- psychology; Persons with Intellectual Disabilities -- rehabilitation; Social Support; Learning Disabilities; Intellectual Disability; Troubles de l'apprentissage.; Enfants en difficulté d'apprentissage.; Déficience intellectuelle; intellectual disability; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; POLITICAL SCIENCE -- Public Policy -- Social Security; Intellectual disability; Learning disabilities; Learning disabled children